2020
DOI: 10.1371/journal.pone.0241845
|View full text |Cite
|
Sign up to set email alerts
|

Tiered healthcare in South Africa exposes deficiencies in management and more patients with infectious etiology of primary adrenal insufficiency

Abstract: Objective We wished to determine the prevalence, etiology, presentation, and available management strategies for primary adrenal insufficiency (PAI) in South Africa (SA), hypothesizing a prevalence greater than the described 3.1 per million. There is great inequity in healthcare allocation, as two parallel healthcare systems exist, potentially modifying PAI patients’ clinical profiles, private being better resourced than public healthcare. Methods An online survey of physicians’ experience relating to PAI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…The majority (66%) of our cohort suffered from at least one crisis in the previous 5 years, which is considerably higher than reported by Meyer et al [6], in which there is a 5%-17% likelihood of having an AC and 6 per 100 patient years, as described by Arlt et al [7]. Explanations for this vastly increased risk in SA are not apparent, but low doctor patient ratios, competing communicable disease demands, poor allocation of health-care resources, and unmet needs, may account for this [19]. Patients living in SA are at increased vulnerability, due to their poor economic circumstances, exposure to suboptimal healthcare delivery, and widespread crime.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The majority (66%) of our cohort suffered from at least one crisis in the previous 5 years, which is considerably higher than reported by Meyer et al [6], in which there is a 5%-17% likelihood of having an AC and 6 per 100 patient years, as described by Arlt et al [7]. Explanations for this vastly increased risk in SA are not apparent, but low doctor patient ratios, competing communicable disease demands, poor allocation of health-care resources, and unmet needs, may account for this [19]. Patients living in SA are at increased vulnerability, due to their poor economic circumstances, exposure to suboptimal healthcare delivery, and widespread crime.…”
Section: Discussionmentioning
confidence: 78%
“…The prevalence of AC varies, depending on the country and in South Africa, the reported a prevalence is 15% [18]. Both a cross-sectional case nding study in South Africa and a nationwide online questionnaire, revealed a prevalence of 15% [19]. This may be under-recognised, due to a discordance in the proportion of patients with compatible symptoms, with an AC and an ultimate diagnosis of an AC.…”
Section: Introductionmentioning
confidence: 99%
“…The high background population of HIV and tuberculosis in Africa may also contribute to this underdiagnosis, as symptoms of PAI may be misconstrued as being associated with these aforementioned communicable diseases [ 12 ]. In a survey of physicians managing patients with PAI in South Africa, though not designed to determine the prevalence, we inferred a prevalence of 14.2 per million [ 13 ]. This prevalence is much lower than the reported 144 per million in Western countries [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…[22] This is particularly relevant to clinical practice in developing regions of the world, where more challenges have been observed. [13,14] The German study came from a specialized endocrine department which limits the generalizability. In contrast, our study included both endocrinologists and nonendocrinologists, giving a more representative sample of doctors whom AI patients may face at the time of stress.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Significant barriers to diagnosis and management of AI were identified in some developing regions of the world with indicators of tiered healthcare that may expose deficiencies in management. [13,14] Therefore, we aimed to examine AI management's current knowledge and perceptions among a sample of physicians from the Middle East and North Africa (MENA) region and in various specialties. Our long-term goal is to identify critical deficiencies in AI Introduction: Treatment of adrenal insufficiency (AI) requires correct lifelong use of glucocorticoids (GCs) with early dose adjustments to cover the increased demand in stress to avoid life-threatening emergencies.…”
mentioning
confidence: 99%